2001
DOI: 10.1523/jneurosci.21-24-09724.2001
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent Plasticity of Mouse Visual Cortex in the Absence of the Neuronal Activity-Dependent Markeregr1/zif268

Abstract: Neuronal activity elicits a rapid increase in the expression of several immediate early genes (IEGs). To clarify a role for IEG response in activity-dependent development, we examined the contribution of the egr1/zif268 gene during visual cortical processing and plasticity in mice. We first analyzed the expression of egr1 mRNA in wild-type (WT) mice using Northern blot hybridization. In the visual cortex, expression of egr1 mRNA increased dramatically after eye opening, systemic injection of kainate, or 30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 69 publications
1
39
0
Order By: Relevance
“…Our sequence analysis also found a well-conserved consensus binding site for Egr-1 within the CG rich region. Egr-1 has many roles including the regulation of neuronal genes in response to neuronal activity and its expression is strongly activated during neuronal differentiation in vivo and in our ES cell differentiation system (Mataga et al, 2001;McMahon et al, 1990 and data not shown). This suggests that this factor may be involved in the upregulation of the Viaat core promoter during differentiation.…”
Section: Discussionmentioning
confidence: 78%
“…Our sequence analysis also found a well-conserved consensus binding site for Egr-1 within the CG rich region. Egr-1 has many roles including the regulation of neuronal genes in response to neuronal activity and its expression is strongly activated during neuronal differentiation in vivo and in our ES cell differentiation system (Mataga et al, 2001;McMahon et al, 1990 and data not shown). This suggests that this factor may be involved in the upregulation of the Viaat core promoter during differentiation.…”
Section: Discussionmentioning
confidence: 78%
“…Candidate plasticity factors have often been linked to a critical-period mechanism by DR (1). Yet simply because a molecule is regulated by activity does not mean that it is involved in plasticity, as shown recently for the immediate early gene zif268 (38). Both DR that is too short to prolong the critical period (12)(13)(14) and DR after visual experience has already begun (48) can still regulate expression of NR2A, which is most consistent with plasticity for orientation lasting into adulthood (49,50).…”
Section: Discussionmentioning
confidence: 79%
“…For Western blot analysis, visual cortices from halothane-anesthetized WT mice were dissected and homogenized by sonication (38). Total protein concentrations were determined by colorimetric (Bradford) assay system (Bio-Rad) and used to normalize loading.…”
Section: Methodsmentioning
confidence: 99%
“…As a further measure of neuronal activation, we quantified expression of the sensory marker egr-1͞zif268 (25), an immediate early gene whose response is up-regulated in GAD65 KO mouse visual cortex (18). In WT animals (Fig.…”
Section: Resultsmentioning
confidence: 99%